Tinjauan Literature: Mengeksplorasi Faktor-Faktor yang Memotivasi Generasi Z untuk Bekerja - Purnama Dewi's, Ari; Rahayu Indrawati, Komang (IPB University, 2025)
Generation Z has increasingly entered the workforce and is projected to succeed Generations X and Y in the organizational landscape. Motivation is recognized as a critical factor influencing their work performance. However, existing research indicates that Generation Z exhibits lower levels of engagement motivation than preceding generations, which contributes to difficulties sustaining long-term employment. This phenomenon warrants closer examination, given the strategic importance of Generation Z as the future workforce. Accordingly, this study aims to identify and analyze the factors influencing work motivation among Generation Z through a systematic literature review (SLR), following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework as the methodological foundation. Literature was sourced from Google Scholar and Crossref using Harzing’s Publish or Perish software with the keywords